Renal ischemia/reperfusion injury; from pathophysiology to treatment - Malek, Maryam (J Renal Inj Prev, 2015)
Ischemia/reperfusion injury (IRI) is caused by a sudden temporary impairment of the blood flow to the particular organ. IRI usually is associated with a robust inflammatory and oxidative stress response to hypoxia and reperfusion which disturbs the organ function. Renal IR induced acute kidney injury (AKI) contributes to high morbidity and mortality rate in a wide range of injuries. Although the pathophysiology of IRI is not completely understood, several important mechanisms resulting in kidney failure have been mentioned. In ischemic kidney and subsequent of re-oxygenation, generation of reactive oxygen species (ROS) at reperfusion phase initiates a cascade of deleterious cellular responses leading to inflammation, cell death, and acute kidney failure. Better understanding of the cellular pathophysiological mechanisms underlying kidney injury will hopefully result in the design of more targeted therapies to prevent and treatment the injury. In this review, we summarize some important potential mechanisms and therapeutic approaches in renal IRI.